GAMBARAN FAKTOR KARAKTERISTIK ORANGTUA DALAM PROMOSI KESEHATAN MELALUI PARENTING EDUCATION DI PAUD HOLISTIK INTEGRATIF - Sunarsih, Tri (MEDIA ILMU KESEHATAN, 2015)
Background: Prolonged economic crisis and a wave of total reform caused many women, including mothers, worked as employees. This has impact on children, where they become lonely, being taken care by others, watching TV too much, and playing video or online games. Thus, formal education (schools) and informal education (family) turned out to be less able to provide its share both in terms of the development of personality and character. The program that is being promoted is parenting education to strengthen the role of parents and families in informal education. Parenting education program obtain less participation, due to the lack of information provided about its purpose, benefits and implementation. Moreover, there is also a lack of public awareness of the importance of parenting education. Objective: This research aimed to explore the parents’ characteristics in health promotion through parenting education. Method: The research was conducted in Karanganyar Regency, Central Java. It was a survey-based research with a cross-sectional design. The research relied on questionnaires as the main instrument for primary data collection. Secondary data was obtained from records in the relevant agencies in Karanganyar Regency. Sample consisted of 108 parents, which was taken by purposive sampling technique. Univariate analysis was used to provide frequency distribution. Result: Perception of parents to parenting education was quite well. Motivation of parents to parenting education and parental expectations of children were in good category. Conclusion: The process of health promotion through parenting education was conducted optimally, it was necessary to increase the perception of parents on parenting education. Parents’ motivation can be a major factor to design and implement parenting education program. Keywords: Parents’ characteristics, health promotion, parenting education